Impact of Nitrogen Levels on Some Flower Growth Traits of Several Hibiscus (Hibiscus Sabdarriffa L.) Cultivars - Mareh, Noora Shafea; Al-Refai, Shaimaa Ibrahim Mahmood (American Journal of Biology and Natural Sciences, 2025)
An experiment was conducted in one of the fields affiliated with the Directorate of Agriculture in Diwaniyah Governorate, Abu Al-Fadl Forest Nursery during the 2023-2024 agricultural season, to study the effect of four levels of nitrogen fertilization (40, 80, 120 and 160) kg ha-1, represented by the symbols F1, F2, F3, and F4, respectively, on four hibiscus cultivars (red, white, striped, and black), represented by the symbols V4, V3, V2, and V1, respectively. The experiment was conducted using a split-plot method with a Randomized Complete Block Design, with four replicates. Nitrogen fertilization levels occupied the main plots, while hibiscus cultivars occupied the sub-plots. The results showed that 160 kg N ha-1 level outperformed the other levels in the number of nuts per plant, the number of seeds per nut, and the weight of the sepal leaves. As for the cultivars, the V4 cultivar outperformed the other cultivars in the number of nuts per plant, the number of seeds per nut, and the weight of the sepal leaves.